Giving Moringa Soy Milk on Weight Gain and Upper Arm Circumference of Pregnant Women - Syafaatun Nahdyah; Mardiana Ahmad; Veni Hadju; Suryani As'ad; Jumrah (Jurnal Kesehatan Masyarakat, 2025)
Moringa oleifera leaves are a potential source of micronutrients and bioactive compounds in functional foods and nutraceuticals. This study aims to determine the effect of moringa soy milk on pregnant women’s weight gain and mid-upper arm circumference (MUAC) as indicators of energy and protein nutritional status. This quasi-experimental study was conducted from February to April 2025 in the working area of the Jatibaru Community Health Center, Bima City. It was conducted on 30 pregnant women in their second to third trimesters with a MUAC <23.5 cm. Respondents were divided into two groups: the intervention group accepting 250 ml/day of moringa soy milk for 28 days, and the control group accepting local supplementary food. Data were analyzed using a paired t-test and chi-square tests. The results showed an increase in body weight of 2.00 kg and MUAC of 0.35 cm in the intervention group (p<0.05), higher than in the control group. The content of vegetable protein, iron, calcium, and vitamins in moringa soy milk plays a role in improving the nutritional status of pregnant women. These findings suggest that moringa soy milk may be an effective and affordable dietary intervention to prevent Chronic Energy Deficiency (CED) in pregnant women.